ANALISIS PENGARUH LOAN GROWTH, CAR, NFC DAN BANK SIZE TERHADAP NPL PADA MASA PANDEMI COVID-19 (Studi pada Bank Umum Konvensional yang Tercatat di Bursa Efek Indonesia Periode Q4 2019 – Q2 2021) - Desty Dwi Lestari; R. Djoko Sampurno (Faculty of Economics and Business Diponegoro University, 2022)
The domino effect of the spread of the Covid-19 virus has penetrated the Indonesian banking sector. The economic slowdown, layoffs, and temporary business closures have resulted in increasingly limited income for depositors, which has an impact on increasing credit risk. Therefore, this study was structured to analyze the effect of Loan Growth (LG), Capital Adequacy Ratio (CAR), Net Fee Commission Income (NFC) and Bank Size (SIZE) on Non Performing Loans (NPL) during the Covid-19 pandemic. The data analysis method in this study uses the Ordinary Least Square (OLS) regression method which includes the classical assumption test, the coefficient of determination test (R2), the stimulant test (F), and the hypothesis test (t). The sample in this study is 29 Conventional Commercial Banks listed on the Main Board Index of the Indonesia Stock Exchange (IDX). The research data is sourced from quarterly published reports and Bloomberg data for each bank from Q4 2019 to Q2 2021. This study shows that all independent variabels have an effect of 17.4% on the dependent variabel. Partially Loan Growth, Capital Adequacy Ratio (CAR), and Bank Size (SIZE) have a negative effect on NPL. Meanwhile, the Net Fee Commission Income (NFC) variabel partially has a positive effect on NPL.